ANALISIS FAKTOR PENENTU ADOPSI CLOUD COMPUTING PADA LAYANAN KESEHATAN - Mohammad Bhanu Setyawan (Universitas Widyatama, 2016)
[Id]Artikel ini bertujuan untuk mengetahui faktor-faktor penentu adopsi cloud computing di rumah sakit Muhammadiyah di Jawa Timur dengan menggunakan Technology Acceptance Model (TAM). ?Sampel yang digunakan dalam penelitian ini adalah 29 sampel rumah sakit dengan alat analisis yang digunakan untuk membangun model adalah: perceived ease of use, perceived usefulness, security effectiveness, reliabilty, needs, cost effectiveness, top management support, complexity, behavioral intention to use dan actual usage. ?Evaluasi goodness of fit dan resampling bootstraping digunakan untuk menganalisis kelayakan model. Evaluasi goodness of fit model struktural diukur menggunakan nilai predictive-relevance diperoleh nilai sebesar = 0,95 yang artinya model memiliki nilai prediktif yang sangat baik. Hasil olah data diperoleh dengan menggunakan resampling bootstraping dengan menghitung hubungan antar variabel memiliki nilai t- hitung yang lebih besar = 2.01 dalam adopsi cloud computing di rumah sakit Muhammadiyah di Jawa Timur. Hasil analisis data diperoleh enam variable mempunyai pengaruh positif dan signifikan dalam adopsi cloud computing, yaitu: Perceived usefulness, Perceived ease of use, complexity, needs, top management support dan behavioral intention to use. Selain itu ada tiga variabel secara positif namun tidak signifikan dalam adopsi cloud computing, yaitu: Security effectiveness, reliability dan cost effectivenessKata kunci: cloud computing, needs, technology acceptance model, top management support, behavioral intention to use, partial leastsquare?[En]?This article aims to determine the factors influencing the adoption of cloud computing in the hospital by using Technology Acceptance Model (TAM). The sample used in this study is 29 samples hospital with an analysis tool used to build the model are: perceived ease of use, perceived usefulness, security effectiveness, reliabilty, needs, cost effectiveness, top management support, complexity, behavioral intention to use and actual usage. Evaluation of the goodness of fit and bootstrapping resampling is used to analyze the feasibility of this model. Evaluation of the goodness of fit of the structural model is measured using a predictive value-relevance obtained a value of = 0.95 which means that the model has predictive value was very good. Results if the data is obtained using bootstrapping resampling by calculating the relationship between variables have the value t count bigger = 2.01 in the adoption of cloud computing in the Muhammadiyah hospital in East Java. Results of data analysis obtained six variables have positive and significant influence in the adoption of cloud computing, namely: Perceived usefulness, Perceived ease of use, complexity, needs, top management support and behavioral intention to use. In addition there are three of these variables is positive but not significant in the adoption of cloud computing, namely: Security effectiveness, reliability and cost effectivenessKeywords: cloud computing, needs, technology acceptance model, top management support, behavioral intention to use, partial leastsquare